2017
DOI: 10.1007/s40195-017-0603-6
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Electroless Ni–P/Ni–Mo–P Duplex Coating with Different Thickness Combinations

Abstract: In this work, a novel duplex Ni-P/Ni-Mo-P coating upon the aluminum (Al) substrate was synthesized via an electroless plating, i.e., the binary Ni-P coating as a transition layer and the ternary Ni-Mo-P coating on the top. It was found that the duplex coating was of a high hardness, large elastic modulus, low porosity and excellent corrosion resistance. In addition, experimental results revealed that for a total 20 lm coating thickness, the duplex coating with a 7 lm of the Ni-Mo-P coating exhibited the best c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 32 publications
2
12
0
1
Order By: Relevance
“…As one can observe, all the spectra are similar and show nickel (Ni), phosphorous (P) and molybdenum (Mo) elements corresponding to XRD analysis. The element composition of the coatings is ~ 84.8% Ni [34], while P content is ~ 1.9%, which corresponds to low P (1-5%) coating [30,46], and ~ 13.3% Mo. According to Guo et al [46], there is a direct relation between P content and crystallinity of Ni-P coating due to the low solubility of P in Ni.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As one can observe, all the spectra are similar and show nickel (Ni), phosphorous (P) and molybdenum (Mo) elements corresponding to XRD analysis. The element composition of the coatings is ~ 84.8% Ni [34], while P content is ~ 1.9%, which corresponds to low P (1-5%) coating [30,46], and ~ 13.3% Mo. According to Guo et al [46], there is a direct relation between P content and crystallinity of Ni-P coating due to the low solubility of P in Ni.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the hypophosphite source of P is known for the reducing property [29]. For improving the mechanical properties such as hardness and corrosion resistance, Mo can be added during electroless plating to form a ternary alloy [30] given its anti-pitting properties [31,32]. Besides, Mo can enhance stability and solubility in the Ni phases and enhance the thermal stability [24,33,34].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanical and tribological properties of the coatings can be improved by the uniform dispersion of such composites [6]. The corrosion resistance of the electroless nano-composite coatings such as Ni-Fe-P [7], Ni-P-TiO 2 [8], ternary alloys of Cu/Zn/Sn with Ni-P coating [9], Ni-P-nano-SiO 2 composite coating [10], Ni-P-PTFE [11], SiC-NiP coatings [12] and Ni-Mo-P [13] would be better than that of the bare Ni-P coating. The nano-composite incorporation can also enhance tribological and metallurgical properties of the Ni-P coatings.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12][13][14] The results showed that biomass can reduce manganese oxide of the ore at temperatures below 600 o C with a degree of reduction more than 95 %. For example, Cheng et al [8] reported that low-grade manganese dioxide ores can be totally reduced by biomass cornstalk at 500 °C.…”
Section: Introductionmentioning
confidence: 99%